Pengembangan Video Animasi Powtoon Sebagai Media Pembelajaran Bahasa Inggris Usia Sekolah Dasar di Masa Pandemi - Nor Laili Fatmawati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
Various adaptations and innovations should be done in the English learning process during the Covid-19 pandemic, especially for elementary school students who are not familiar with the distance learning system. This study aims to develop a Powtoon-based animated video as an English learning medium for elementary school students during the Covid-19 pandemic. The animation video was developed using the ADDIE model which includes the analysis, design, development, implementation and evaluation stages. This research produces an audiovisual learning media in form of animated videos that have been tested by media experts, material experts, and have gone through small group and field trials. The test results indicate the feasibility of this product is 4.80 in the Very Eligible category. Thus, the animated Powtoon-based video is worthy product as an alternative learning medium in English distance learning classes for elementary school students during the pandemic.